Core skills provision in higher education. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2007)
Concerns about poor level of skills in the workforce and perceptions of a mismatch between the actual competencies of young graduates and those required by employers is an issue that has been widely discussed in the Malaysian media. A study on graduates’ unemployment conducted by the National Higher Education Research Institute (2003) highlights employers’ dissatisfaction with the level of the graduates’ abilities with regards to communication skills, interpersonal skills, problem solving skills and their initiative and proactive skills.